Pengaruh Pupuk Anorganik Terhadap Pertumbuhan dan Hasil Kacang Hijau (Vigna radiata L.) Varietas Vima 1 dan Jumbo - Abinowo, Bondan; Maryani, Yekti; Pamungkas, Djoko Heru (Universitas Sarjanawiyata Tamansiswa, 2023)
Green beans are one of the food commodities that are widely consumed by Indonesian people. Indonesia's mung bean productivity decreases every year due to the ineffective use of inorganic fertilizers and the use of inappropriate varieties. The use of appropriate and efficient inorganic fertilizers and varieties is considered capable of supporting the productivity of green beans. The purpose of this study was to determine the interaction between various inorganic fertilizer treatments and varieties on the growth and yield of green beans. The research was conducted in September - December 2022 in Bungkus Hamlet, Parangtritis Village, Kretek District, Bantul Regency, Special Province of Yogyakarta. The study was arranged in Complete Randomized Block Design (RAKL) which consisted of 2 factors, namely types of inorganic fertilizers with 4 levels (NPK, NP, NK, and PK) and varieties with 2 levels (Vima 1 and Jumbo). Analysis of the results using Duncan's Multiple Range Test (DMRT) at 5% level. The results showed that there was no interaction between the types of inorganic fertilizers and varieties on the growth and yield of green bean plants. Mixed NPK inorganic fertilizer treatment gave the highest green bean yield. Vima 1 green bean variety treatment gave the highest yield.